Pengaruh Kepemimpinan dan Komunikasi terhadap Kinerja Karyawan pada PT. Baby Bar Indonesia - Setiawan, Rio; Siamto, Wahadi; Ratnawati , Whina (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of leadership style and communication on employee performance at PT. Baby Bar Indonesia. The background of the research is based on the crucial role of leadership and communication in improving work effectiveness and organizational competitiveness amid globalization and technological advancement. This research employs a quantitative approach with an associative method. The population consists of all employees of PT. Baby Bar Indonesia, totaling 50 individuals, with a saturated sampling technique. Data were collected through questionnaires and interviews, and analyzed using validity tests, reliability tests, simple and multiple linear regression, as well as t-tests and F-tests. The results indicate that both leadership style and communication significantly influence employee performance, both partially and simultaneously. A participative leadership style and effective communication were found to enhance employee motivation and work productivity. The study recommends improving two-way communication patterns and implementing a more open and supportive leadership approach to optimize employee performance.